A rural health supplement to the hookworm intervention in the American South - Jonathan Fox; Theocharis Grigoriadis (Freie Universität Berlin, School of Business & Economics, 2018)
This project re-investigates the hookworm eradication efforts of the Rockefeller Foundation's Sanitary Commission (RSC) in the American South during the Progressive Era. The RSC worked to eradicate hookworm across 11 southern states between 1911 and 1915, efforts that have been linked to dramatic short- and long-term increases in human capital and labor productivity. Although useful from an identification standpoint, these single-shot interventions, in the absence of cooperative efforts to improve underlying conditions, have a mixed record of long-term effectiveness across public health research. The efficacy of deworming campaigns in particular has come under extensive scrutiny. The experience of the American South had stood as example of how a single-shot hookworm eradication program has improved outcomes; however, the robustness of this result has also recently come into question. A replication of the Bleakley (2007) seminal work investigating hookworm eradication finds faults with the robustness and interpretations of the results (Roodman 2017), and an investigation into the activities of the RSC has determined them unevenly distributed across hookworm-affected areas (Elman et. al 2013). Perhaps not coincidentally, the RSC's hookworm eradication program was not the only public health intervention that occurred in the rural South during the Progressive Era. Rural public health centers spread throughout the American South during this period, partially backed by the Rockefeller Foundation. Given the use of difference-in-difference methods using decennial census data, and the participation of the Rockefeller Foundation in the funding of these rural health centers, this is a potentially critical omission in the evaluation of the RSC efforts. In this project, we investigate the connection between these rural health centers and the Rockefeller Foundation's hookworm eradication efforts, consider whether their presence explains effects attributed thereto, and examine their importance as a follow-up program to the initial hookworm intervention.
Keywords: I15; I18; N32; O15; O51; P51; 330; Rockefeller Sanitary Commission; hookworm eradication; Deworming; Economic Development; County Health Organizations; human capital; Progressive Era